Zuhud dan Implementasinya pada Pondok Pesantren Al-Musyahadah - Ai Rahmi (Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2022)
This research is motivated by the importance of zuhud attitude in everyday life, especially in the boarding school environment. This study aims to examine the inculcation of zuhud and its implementation in the Al-Musyahadah Islamic boarding school. This study uses a qualitative approach and uses descriptive analysis methods. Zuhud is emptying the heart of the world's desire to always draw closer to Allah. Inculcating zuhud by growing understanding for students to accept all the provisions of Allah that comes to themselves. The implementation of zuhud can be distinguished from its characteristics, namely the nature and behavior of the zuhud person. This study concludes that at the Al-Musyahadah Islamic boarding school there is the inculcation of the attitude of zuhud as evidenced by the studies of books that discuss zuhud in the Al-Musyahadah Islamic boarding school such as Nashoihul Ibad, Sirr al-Asror, Al-Hikam and the implementation of zuhud from students of Al-Musyahadah Islamic boarding school can be seen from their daily lives such as having good morals in socializing and others. However, in practice there are still students who find it difficult to implement zuhud.